Engineering and optimization of the 2‐phenylethylglucosinolate production in Nicotiana benthamiana by combining biosynthetic genes from Barbarea vulgaris and Arabidopsis thaliana. (22nd March 2021) - Wang, Cuiwei; Crocoll, Christoph; Agerbirk, Niels; Halkier, Barbara Ann
Summary: 2‐Phenylethylglucosinolate (2PE) derived from homophenylalanine is present in plants of the Brassicales order as a defense compound. It is associated with multiple biological properties, including deterrent effects on pests and antimicrobial and health‐promoting functions, due to its hydrolysis product 2‐phenylethyl isothiocyanate, which confers 2PE as a potential application in agriculture and industry. In this study, we characterized the putative key genes for 2PE biosynthesis from Barbarea vulgaris W.T. Aiton and demonstrated the feasibility of engineering 2PE production in Nicotiana benthamiana Domin. We used different combinations of genes from B. vulgaris and Arabidopsis thaliana (L.) Heynh. to demonstrate that: (i) Bv BCAT4 performed more efficiently than At BCAT4 in biosynthesis of both homophenylalanine and dihomomethionine; (ii) MAM1 enzymes were critical for the chain‐elongated profile, while CYP79F enzymes accepted both chain‐elongated methionine and homophenylalanine; (iii) aliphatic but not aromatic core structure pathway catalyzed the 2PE biosynthesis; (iv) a chimeric pathway containing Bv BCAT4, Bv MAM1, At IPMI and At IPMDH1 resulted in a two‐fold increase in 2PE production compared with the B. vulgaris‐ specific chain elongation pathway; and (v) profiles of chain‐elongated products and glucosinolates partially mirrored the profiles in the gene donor plant, but were wider in N. benthamiana than in the native plants. Our study provides a strategy to produce the important homophenylalanine and 2PE in a heterologous host. Furthermore, chimeric engineering of the complex 2PE biosynthetic pathway enabled detailed understanding of catalytic properties of individual enzymes – a prerequisite for understanding biochemical evolution. The new‐to‐nature gene combinations have the potential for application in biotechnological and plant breeding. Significance Statement: In this study, we engineered the production of the multifunctional 2‐phenylethylglucosinolate by heterologous expression in Nicotiana benthamiana using genes from Barbarea vulgaris and Arabidopsis thaliana, and we infer the substrate specificities of MAM1 and CYP79F enzymes by chimeric engineering of the complex biosynthetic pathway. The work provides basic knowledge on biochemical evolution of these enzymes and constitutes an important step towards unfolding the biotechnological and plant breeding potentials of 2‐phenylethylglucosinolate.